Acrodermatitis enteropathica: a case report - Shakya, Nabin Bhakta; Rajbhandari, Sudarsan Lal; Jha, Sagar Mani (Medical Journal of Shree Birendra Hospital, 2012)
Acrodermatitis enteropathica is rare congenital autosomal recessive disorder. Premature are particularly risk and disease is caused by zinc deficiency due to a specific absorptive defect. This disease manifests in child as peevish, withdrawn and photophobia and develop vesicobullous dermatitis on hands, feet and perioroficial areas and alopecia. Diarrhea is often present. This also presents as shunted growth and decrease resistance to infection. Poor wound healing. A low plasma zinc level and Serum alkaline phosphatase are useful indicator of zinc status. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6461 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 32-34